Synthesis of TiO2-Activated Carbon from Coffee Dregs by Hydrothermal Method for Photodegradation of Diazinon - Haryati, Tanti; Zakaria, Helmy Ahmad; Sutisna, Sutisna; Suwardiyanto, Suwardiyanto; Sulistiyo, Yudi Aris; Andarini, Novita (Molekul, 2025)
ABSTRACT. The photocatalytic activity of TiO₂ can be enhanced by binding it to materials with high adsorption capacity. The synthesis began with the mixture of 5 mL TTIP, 30 mL ethanol, and H₂O 30 mL stirred for 1 hour. Activated carbon made from coffee grounds in varying amounts (5 g, 10 g, and 15 g) was then added to the TTIP solution, and the mixture was stirred for 2 hours. The mixture was then placed in an autoclave, heated at 180°C for 12 hours, dried, and then calcined at 500°C for 3 hours. SEM morphological analysis showed that TiO₂ particles were attached to the surface of the activated carbon, which was further confirmed by EDX data showing the presence of Ti and O elements in the synthesized material. Furthermore, crystallinity and gap analyses demonstrated that the material was exclusively in the anatase phase. The largest surface area, 286.10 m²/g, was observed on titanium dioxide-activated carbon/10 (TiO₂-AC/10), exhibiting a mesoporous structure and microporous features. Photocatalytic tests for diazinon degradation demonstrated that TiO₂-AC/10 exhibited the most significant photocatalytic activity of 65.18%. The composite material's degradation capability diminished by 9-13% from the initial to the third cycle. The residual titanium elements within the composite material maintained stability, suggesting the integrity and durability of TiO₂ particles affixed to the surface of activated carbon. Keywords: TiO2-AC, Coffee Dregs, Diazinon, Photocatalysis, Reusability